2010
DOI: 10.1007/s11130-010-0167-3
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid Content of Commonly Consumed Herbs and Assessment of Their Bioaccessibility Using an In Vitro Digestion Model

Abstract: Herbs are a rich source of bioactive phytochemicals such as carotenoids, which are known to exert various positive biological effects. However, there is very limited information in the literature regarding the content and bioavailability of carotenoids from commonly consumed herbs. Therefore, the objectives of the present study were first, to determine the carotenoid content of eight herbs namely basil (Ocimum basilicum), coriander (Coriandrum sativum), dill (Anethum graveolens), mint (Metha L.), parsley (Petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 46 publications
2
32
3
2
Order By: Relevance
“…Many bioactive phytochemicals have been previously identified including flavonoids such as apiin and luteolin and carotenoids in Pc (Karimi, 2012;Daly et al, 2010), and catechol, salicylic acid, glycitin, pyrogallol, gentisic acid, protocatechiuic acid, quinic acid, caffeic acid, ferulic acid, gallic acid, and chlorogenic acid in Cs (Wangensteen et al, 2004;de Almeida Melo et al, 2005;Bajpai et al, 2005). Many of these are phenolic compounds that have been demonstrated as potential treatments for diverse physiological pathologies.…”
Section: Inhibitory Effects Of Pc and Cs On Micronucleus Inductionmentioning
confidence: 99%
“…Many bioactive phytochemicals have been previously identified including flavonoids such as apiin and luteolin and carotenoids in Pc (Karimi, 2012;Daly et al, 2010), and catechol, salicylic acid, glycitin, pyrogallol, gentisic acid, protocatechiuic acid, quinic acid, caffeic acid, ferulic acid, gallic acid, and chlorogenic acid in Cs (Wangensteen et al, 2004;de Almeida Melo et al, 2005;Bajpai et al, 2005). Many of these are phenolic compounds that have been demonstrated as potential treatments for diverse physiological pathologies.…”
Section: Inhibitory Effects Of Pc and Cs On Micronucleus Inductionmentioning
confidence: 99%
“…One of the widely used vegetal species in various nations' medicine is parsley (Petroselinum crispum), which has remedial effects as a powerful diuretic agent [1,2], an abortifacient [3][4][5] and an expectorant [6,7]. Parsley is a native herb of the central Mediterranean region (southern Italy, Algeria and Tunisia), which is in the Apiaceae family, and is a species of Petroselinum [8].…”
Section: Parsley and Immunomodulationmentioning
confidence: 99%
“…Daly et al observed bioactive phytochemicals, including carotenoids, in parsley [6]. Carotenoids were shown to be associated with a low risk of several human chronic disorders including age-related macular degeneration and certain cancers.…”
Section: Parsley and Immunomodulationmentioning
confidence: 99%
“…It is seasonal fruit and rich in phelonics. The phenolic compounds are useful for preventing some diseases like cardiovascular and inflammatory diseases and carotenoids avoid age-related macular degeneration (Scalbert and Williamson, 2000;Daly, et al, 2010). Vitamin C is useful for reducing the risk of several cardiovascular, neurodegenerative diseases (Harrison and May, 2009).…”
Section: Introductionmentioning
confidence: 99%